STUDY ON SEMEN CHARACTERISTICS OF CHOTTANAGPURI RAMS - BHARTI, M K; SINHA, M P; SINGH, BALRAJ; MAHTO, DINESH (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted on the semen characteristics of six Chottanagpuri rams. Thecolour of Chottanagpuri ram semen was found to be creamy or creamy white. The overall mean ejaculatevolume, mass-motility, sperm concentration, live sperm percentage and abnormal sperm percentagewere found to be 0.648±0.027 ml, 4.222±0.144, 3793±0.134 millions/ml, 83.333±1.318 and 7.034±0.135,respectively. The difference between the ejaculate volume, mass motility, sperm concentration, livesperm percentage and abnormal sperm percentage were found to be non -significant among the rams.
Keywords: Semen; Chottanagpuri rams